2014
DOI: 10.3109/0886022x.2014.991263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on the serum levels of pro-inflammatory cytokines and tissue injury after renal ischemia reperfusion in rats

Abstract: We investigated the changes in the serum levels of tumor necrosis factor (TNF)-a and interleukin (IL)-6, the pro-inflammatory cytokines, and the possible effect of melatonin on the modulation of these inflammatory molecules after renal ischemia reperfusion (IR). The study was carried out in the laboratory of Department of Pharmacology. Forty-six male Wistar albino rats were divided into five groups as control (n ¼ 6), positive control (n ¼ 4), sham (n ¼ 12), renal IR (n ¼ 12), and renal IR melatonin (n ¼ 12). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…Rutaecarpine treatment inhibits the production of inflammatory cytokines in renal tissue. The inflammatory cytokines secreted by renal endothelial cells and parenchymal cells are important markers of the inflammatory response following IRI (30). As shown in Table III, when compared with the sham group, levels of the inflammatory cytokines NF-κB, TNF-α, IL-6 and ICAM-1 increased in the renal tissues of rats in the IRI, NS, Ru-30 and Ru-60 groups (P<0.05) compared with the sham group, indicating that inflammatory factors were released from the renal tissue during the early stage of IRI.…”
Section: Resultsmentioning
confidence: 99%
“…Rutaecarpine treatment inhibits the production of inflammatory cytokines in renal tissue. The inflammatory cytokines secreted by renal endothelial cells and parenchymal cells are important markers of the inflammatory response following IRI (30). As shown in Table III, when compared with the sham group, levels of the inflammatory cytokines NF-κB, TNF-α, IL-6 and ICAM-1 increased in the renal tissues of rats in the IRI, NS, Ru-30 and Ru-60 groups (P<0.05) compared with the sham group, indicating that inflammatory factors were released from the renal tissue during the early stage of IRI.…”
Section: Resultsmentioning
confidence: 99%
“…In several animal models of chronic kidney disease, involving experimental hypertension, diabetes mellitus and various models of nephrotoxicity (Hrenak et al, 2015). Mel treatment reversed the increase of serum TNF-α levels and histopathological injury in renal tissue after renal IR (Oguz et al, 2015). Mel, with a dose of 40 mg/kg, has the potential to reduce MTX induced oxidative stress, neutrophil infiltration as well as renal damage (Abraham et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Mel treatment reduces renal injury by reducing lipid oxidation and NO production in STZ-induced diabetic rats exposed to IR (Kurcer et al, 2007). In our previous study we found that Mel treatment reversed the increase of serum tumor necrosis factor-alpha (TNF-α) levels and histopathological injury in renal tissue after renal IR (Oguz et al, 2015). It has been reported that Mel has the potential to reduce MTX induced oxidative stress, neutrophil infiltration as well as renal damage at a dose of 40 mg/kg in rats (Abraham, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…This connection of inflammatory cytokines in renal IRI-induced remote organ dysfunction has been corroborated by critical roles of cytokines in modulating the remote organ lung effects during AKI (21). Serum pro-inflammatory cytokines such as TNF-α levels increase significantly in renal IR (22). These circulatory inflammatory cytokines transferred to other organs such as lung (9) and probably heart, that may cause apoptosis in this tissues.…”
Section: Discussionmentioning
confidence: 87%